Predictive control of an activated sludge process: An application to the Viikinmäki wastewater treatment plant. (November 2015) - Mulas, Michela; Tronci, Stefania; Corona, Francesco; Haimi, Henri; Lindell, Paula; Heinonen, Mari; Vahala, Riku; Baratti, Roberto
Abstract : Highlights: Multivariable predictive control for optimisation of wastewater treatment plant operation. The aim is to improve nitrogen removal efficiency while reducing the energy consumption. Effective predictive control with a simple dynamic matrix control strategy. Simulation results show the potential of the control strategy for on-line implementation. Abstract: In this work, we discuss the application of multivariable predictive control for the activated sludge process in a full-scale municipal wastewater treatment plant. Emphasis is given to the selection of a control configuration that contributes to minimising the economic costs while improving the removal efficiency of the nitrogen compounds. For this task, a simple dynamic matrix control algorithm is favoured for controlling the nitrogen concentrations at the end of the biological process. The behaviour of the activated sludge process is reproduced in a commercial simulator that acts as a real-time testing platform and that is also used for identifying the multivariable input–output models for the predictive controller. For demonstrating the effectiveness of the proposed approach, different control configurations are considered and compared against the aeration control strategies currently used at the plant. Based on the simulation results, this work shows the potentiality of the dynamic matrix control which is able to decrease the energy consumption costs and, at the same time, reduce the ammonia peaks and nitrate concentration in the effluent.